It's a boy! Women and non-monetary benefits from a son in India - Laura Zimmermann (Institute for the Study of Labor (IZA), 2012)
Son preference is widespread in a number of developing countries. Anecdotal evidence suggests that women may contribute to the persistence of this phenomenon because they derive substantial long-run non-monetary benefits from giving birth to a son in the form of an improvement in their intra-household position. This paper tests this hypothesis in the Indian context. The results suggest that for the most part there is little evidence of substantial female benefits, and any positive impacts of having a son disappear after six months. This implies that the female-specific self-interest in a son is probably much lower than commonly assumed.
Keywords: D13; J12; J13; J16; 330; son preference; non-monetary benefits; bargaining power; intra-household allocation; India; Jungen; Präferenztheorie; Familienökonomik; Frauen; Verhandlungsmacht; Indien